Incidence and risk factors for cancer in people with type 1 diabetes, stratified by stages of diabetic kidney disease: a nationwide Finnish cohort studyResearch in context - Maija Feodoroff; Valma Harjutsalo; Sari Mäkimattila; Per-Henrik Groop (Elsevier, 2024)
Summary: Background: Individuals with type 1 diabetes (T1D) have been reported to have increased overall risk of cancer. In addition, individuals with a kidney transplant/transplantation (KT) have markedly increased cancer risk due to chronic use of immunosuppressive agents. However, it has not been elucidated whether the observed excess cancer risk is related to KT or whether diabetic kidney disease (DKD) per se is a risk factor for cancer in individuals with T1D. Methods: The study included 5035 individuals from the Finnish Diabetic Nephropathy Study (FinnDiane) and 14,061 control individuals without diabetes. We assessed the standardized incidence ratios (SIRs) for cancers in individuals with T1D compared to controls according to DKD status. Cox regression analyses were used to identify potential risk factors for cancer in individuals with type 1 diabetes. Findings: The SIR for overall cancer for all participants was 1.14 (1.05-1.24), for participants without KT 0.92 (0.83-1.01) and for participants with KT 4.78 (4.02-5.64). Participants without KT had in fact a reduced risk of prostate cancer with a SIR of 0.54 (0.37-0.76), cancer of urinary organs 0.41 (0.21-0.73) and respiratory and intrathoracic organs, 0.62 (0.38-0.97). Participants with KT had on the contrary an increased risk of non-melanoma skin cancer, SIR 14.50 (10.99-18.86), cancer in the lymphoid and hematopoietic tissue 5.38 (2.99-8.96), mouth or pharynx 5.13 (2.08-10.66), melanoma 5.12 [2.38-9.72]) and respiratory and intrathoracic organs 2.77 (1.21-5.49). The risk of thyroid cancer was increased both in participants without KT, SIR 2.14 (1.39-3.16) and with KT 5.30 (1.68-12.78). Interpretation: The excess overall cancer risk in individuals with type 1 diabetes is only seen in KT recipients and in thyroid cancer. The individuals without KT seem to have a decreased risk of some forms of cancer. Funding: Folkhälsan Research Foundation, Academy of Finland [316664], Wilhelm and Else Stockmann Foundation, Liv och Hälsa Society, Novo Nordisk Foundation [NNF OC0013659], Finnish Foundation for Cardiovascular Research, Finnish Diabetes Research Foundation, Medical Society of Finland, Sigrid Jusélius Foundation, and Helsinki University Hospital Research Funds [TYH2018207 and TYH 2020305].